Blockchain Technology Suitability in Inter-Organisational Workflows: A Thematic Review of E-Payment Process in the Malaysian Public Sector - Khairil Faizal Khairi; Naharudin Saadan; Abdullah Mohammed Ahmed Ayedh (USIM Press (Penerbit USIM), 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 1 Page (39–67)